Association Between Low T3 Syndrome and Poor Prognosis in Adult Patients With Acute Myocarditis - Zhao, Yan; Wang, Wenyao; Zhang, Kuo; Tang, Yi-Da (Frontiers in Endocrinology, 2021)
Background: This study aims to investigate the role of free triiodothyronine (fT3) in predicting poor prognosis of adult patients with acute myocarditis. Methods: A total of 173 consecutive adult patients with acute myocarditis completed thyroid function evaluations. They were divided into two groups according to fT3 levels: low fT3 group (n=54, fT3 <3.54 pmol/L) and normal fT3 group (n=119, fT3≥3.54 pmol/L). The primary endpoint was major adverse cardiac events (MACE). Results: During the 3.5±2.8 years follow-up, the rate of MACE was 29.6% versus 3.5% in low fT3 group versus normal fT3 group, respectively (P<0.0001). Long-term at 8 years MACE-free survival were lower in low fT3 group versus normal fT3 group (52.9% versus 92.3%, log-rank P<0.0001), respectively. Univariate Cox analysis showed that LVEF<50% [hazard ratio (HR) 10.231, 95% confidence interval (CI): 3.418-30.624, P<0.0001) and low fT3 level (HR 0.360, 95%CI: 0.223-0.582, P<0.0001) were strongest two predictors of MACE. After adjustment for traditional risk predictors, the prognostic value of fT3 status was still significant (HR 0.540, 95%CI: 0.316-0.922, P=0.024). Compared with normal fT3 group, those in low fT3 group were at a much higher risk of MACE (HR 5.074, 95% CI: 1.518-16.964, P=0.008). Conclusions: Low T3 syndrome was a strong predictor of poor prognosis in adult patients with acute myocarditis. These findings suggest that fT3 level could serve as a biomarker for risk stratification in acute myocarditis patients.